Mitigation of the potential induced degradation of photovoltaic modules and its impact on the performance of solar parks - Jan Vollers (2023)
This master thesis gives an overview of the impact of the potential induced degradation (PID) effect in a portfolio of several multi-megawatt ground-mounted solar parks and how this effect can be prevented and reversed. The so-called photovoltaics power booster (PVPB) box is used, which applies a repair voltage to the array of photovoltaic modules at night and thus reverses the PID effect. One central inverter station is equipped with a PVPB box for each solar park. Its specific yield values are then put into proportion with the specific yield values of the remaining inverter stations representing the reference area. Technical failures of yieldrelevant equipment and days with snowfall are considered and excluded from the evaluation. The results are mixed and show partly positive developments on the yield and partly no development. Most of the PVPB boxes have only been in operation for two to three months during the winter, which is weak in irradiation and makes the evaluation less accurate. The evaluation phase should be extended until at least some months with suitable irradiation are included in the analysis and therefore be repeated in May or June. However, it can be said that the PID effect will remain an existing problem in the future, as the modules will not be built PID-free, and the costs for module production must be kept as low as possible. Furthermore, modules can be labeled as PID-free according to the TS IEC 62804-1:2015-08 tandard if they have power losses due to PID of less than 5%. The effect will probably even increase since the maximum system voltage of new solar parks is up to 1500 V instead of the previous 1000 V.